Population appraisal of health and quality of medical aid as indexes of conducted modernization in public health service - M. S. Khlynin (Бюллетень сибирской медицины, 2009)
Is determined that the population’s attitude to accessibility, quality of charge-free and paid medical services is depended on a financial status, state of health, availability of diseases and age. The paid medical service development will reduce the use of medical aid according to the compulsory medical insurance program that will allow to spend more resources on less wealthy groups of people. The expediency of health indexes monitoring, competitive relations development, motivation in public health service is proved to be necessary.